Development of bifunctional Mo doped ZnAl2O4 spinel nanorods array directly grown on carbon fiber for supercapacitor and OER application. Issue 3 (1st February 2023) - Gouadria, Soumaya; Abudllah, Muhammad; Ahmad, Zahoor; John, Peter; Nisa, Mehar Un; Manzoor, Sumaira; Aman, Salma; Ashiq, Muhammad Naeem; Ghori, Muhammad Ishfaq
Abstract: Electrochemical energy storage and water splitting strategies may be greatly improved with proper structural design and doping techniques. In the present study, molybdenum-doped ZnAl2 O4 loaded on carbon fiber (Mo–ZnAl2 O4 /CF) was fabricated via a simple hydrothermal synthetic approach. Due to its unique hierarchical nanostructures and enhanced electrical, structural topologies, Mo-doped ZnAl2 O4 demonstrates exceptional supercapacitor performance and electrocatalytic oxygen evolution reaction activity. The Mo-doped ZnAl2 O4 electrode material exhibited 1477.63 F g −1 specific capacitance, 46.57 Wh Kg −1 specific energy and specific power of 476.4 W kg −1 at 1 A g −1 . After 5000 cycles, the pseudo supercapacitor retains 97.46% of its capacitance and displays stable behavior over 50 h. During the OER reaction, the Mo–ZnAl2 O4 /CF as an electrocatalyst rapidly self-reconstructs, resulting in many oxygen vacancies, and causes a lower 38 mV dec −1 Tafel slope and overpotential potential of 255 mV to achieved 10 mA cm −2 current flow and responsible for the excellent stability of the electrocatalyst. These findings suggest that multifunctional materials based electrode for electrical energy conversion and storage become more efficient and stable by using Mo for doping to generate porous hierarchical structures and local amorphous phases.